People power the Philippine experience - Pelingon, Fil.; Naval, Eddie; Mayuga, Sylvia; Salvador, Eva G.; Constantino, Gerry; Malimban, Froilan; Velez, Jose Mari.; Communication Foundation for Asia. Electronic Media Division (Manila Communication Foundation for Asia, 1986)
A compact, comprehensive and moving documentary that traces the roots of people power from the assassination of ex-senator Benigno "Ninoy" Aquino to the 4-day triumph by the Camp Crame and Camp Aguinaldo in EDSA. Witnessed by the whole world, the four fateful days of February 22-25, 1986 changed the history of the Filipino nation.
Writer, Sylvia Mayuga ; editing director, Eva G. Salvador ; editor, Gerry Constantino ; music/effects, Froilan Malimban ; narrator, Jose Mari Velez.
DVD. Issued also as VHS.
Keywords: People power; Philippines -- History -- Revolution, 1986.